The Impact of a Mandated Trauma Center Alcohol Intervention on Readmission and Cost per Readmission in Arizona. Issue 7 (July 2015) - Hinde, Jesse M.; Bray, Jeremy W.; Aldridge, Arnie; Zarkin, Gary A.
Abstract : Background: Persons appearing in trauma centers have a higher prevalence of unhealthy alcohol use than the general population. Screening and brief intervention (SBI) is designed to moderate drinking levels and avoid costly future readmissions, but few studies have examined the impact of SBI on hospital readmissions and health care costs in a trauma population. Research Design: This study uses comparative interrupted time-series and the Arizona State Inpatient Database to estimate the effect of the American College of Surgeons Committee on Trauma SBI mandate on the probability of readmission and cost per readmission in Arizona trauma centers. We compare individuals with and without an alcohol diagnosis code before and after the mandate was implemented. Results: The mandate resulted in a 2.2 percentage point reduction (44%) in the probability of readmission. Total health care and readmission costs were not affected by the mandate. Conclusions: The estimates are consistent with a differential effect of SBI: SBI reduces readmissions among those who present with a less serious alcohol-related problem. Persons with more serious alcohol problems are less likely to respond to SBI. These higher risk individuals likely have a higher cost, which may explain the lack of change in readmission costs. Our study is a macrolevel intent-to-treat analysis of SBI's impact that corroborates the potential of SBI implied by efficacy studies in trauma centers and other settings. This study provides a framework for future research involving more states and health systems and evaluating other SBI policies. Abstract : Supplemental Digital Content is available in the text.